A novel two-codon deletion at codon 508 and 509 of the rpoB gene in pulmonary tuberculosis and HIV co-infection: A case report - Lih Huey, Chua Wei Chuan, Zeti Norfidiyati Salmuna Ayub, Norazmi Mohd Nor, Alwi Muhd Besari; Chan, Yean Yean (Pakistan Journal of Medical & Health Sciences, 2022)
We report a case of pulmonary Mycobacterium tuberculosis infection with a resistance to rifampicin (RIF) in a 39-year-old man who was co-infected with Human Immunodeficiency Virus (HIV) and hepatitis C. Phenotypic and genotypic test were performed to diagnose the patient. Sequencing analysis revealed novel two-codon deletion at codon 508 and 509 of the rpoB gene in M. tuberculosis. Keywords: Co-infection, Mycobacterium tuberculosis, rpoB gene, rifampicin-resistant.